Meta Analysis of Health Belief Model Theory on the Predictor of HPV Vaccine Uptake in Women of Reproductive Age - Nurul Qomariah; Bhisma Murti; Uki Retno Budihastuti (Journal of Health Promotion and Behavior, 2024)
Background: Lack of knowledge about the use of HPV vaccine in women of productive age can result in cervical cancer. This study aims to determine the effect of the Health Belief Model application on the predictor of HPV vaccine uptake in women of reproductive age. Subjects and Method: Systematic review and meta-analyses were conducted using PRISMA guidelines and PICO model including: Population = women of reproductive age; Intervention= high perceived benefits, high perceived severity, high perceived susceptibility; Comparison= low perceived benefits, low perceived severity, low perceived susceptibility; Outcome= HPV vaccine uptake. Articles were collected from databases such as PubMed, Science Direct, and Google Scholar. The keywords used in the database search were "Health Belief Model" AND "Human Papilloma Virus" OR "HPV" AND "Women" AND "cross sectional study". A total of 7 articles met the inclusion criteria, namely full-text primary paper, cross-sectional study design, with a measure of association was the Odds Ratio (OR), the study subjects were women of reproductive age, interventions were in the form of high perceived benefits, high perceived severity, high perceived vulnerability, and the outcome was in the form of HPV vaccine use. They were subsequently assessed for meta-analysis using RevMan 5.3. Results: Meta-analysis from Indonesia, Ethiopia, the United Kingdom, Japan, Romania, Spain, and Italy showed that high perceived benefits of HPV vaccine use (aOR= 1.81; 95% CI= 1.00 to 3.26; p= 0.050), high perceived severity (aOR= 1.78; 95% CI= 0.94 to 3.40; p= 0.080), and high perceived susceptibility (aOR= 1.70; CI 95%= 0.75 to 3.83; p= 0. 200) increased the likelihood of HPV vaccine uptake. Conclusion: High perceived benefits, high perceived severity, and high perceived susceptibility have the likelihood of women of productive age to use HPV vaccine